BANTUAN HUKUM KELOMPOK RENTAN - Afifah, Wiwik (DiH: Jurnal Ilmu Hukum, 2020)
Women, children and vulnerable groups are marginalized groups that have many injustice problems especially related with gender. Among them are juducial access difficulties, overty, lack of information, legal illiteracy and others. At present the vulnerable groups have difficulty accessing legal assistance because they are pover and have not been recognized even they cannot be proven because they are not included in the State overty data. Related to this, writer examine the problems and concepts of legal aid for marginalized groups. The results of this sturdy indicate that there is difficulties in accessing legal aid because indonesai still have legal aid bades on economic condition, while other conditions of vulnerability have not been accommodated. Legal aids concept must be transformative to reach all of vulnerable groups regardless of gender status but accommodates vulnerability due to patriarchal system and sosial conflicts.Perempuan, anak dan kelompok rentan adalah kelompok yang termarginalkan dan mengalami banyak problematika ketidakadilan gender. Diantaranya adalah kesulitan akses yudisial, kemiskinan, lack of information, buta hukum dan masih banyak lainnya. Saat ini kelompok rentan kesulitan mengakses bantuan hukum karena kondisi miskinnya belum terakui bahkan tidak bisa dibuktikan karena tidak masuk dalam data kemiskinan Negara. Terkait hal tersebut penulis meneliti tentang problematika dan konsep bantuan hukum bagi kelompok marginal. Adapun hasil penelitian menunjukan adanya kesulitan kases bantuan hukum bagi kelompok rentan karena selama ini bantuan hukum masih berbasis ekonomi atau kondisi ekonomi atau kemiskinan, sedangkan kondiosi kerentanan lainnya belum terakomodir. Konsep bantuan hukum bagi kelompok rentan sedianya bersifat transformatif yaitu menjangkau semua lampiran tanpa memandang status jenis kelamin, namun mengakomodir kerentanan karena sistem patriarki dan konflik sosial.